FROM THE HISTORY OF RATIFICATION OF DOCUMENTS ON THE PREVENTION OF HUMAN TRAFFICKING IN UZBEKISTAN - Қурязова Л. Р. (TARIXIY TADQIQOTLAR, 2025)
The article, based on extensive literature, archival data and legislative acts, states that human trafficking is a multifaceted danger and a serious crime against human rights that robs people of their rights and freedoms, directly threatens their personal integrity and their health, and causes an increase in organized crime worldwide. The article also analyzes the history of the ratification of documents on the prevention of human trafficking in Uzbekistan.